KELEBIHAN DAN KEKURANGAN IMPOR BARANG ASING BAGI NEGARA INDONESIA - Riyanto, Fendi; Christian Sitohang, Arga; Arsita Kusumadewi, Ni Made; Mahindah, Mahindah; Yulia Sari, Firda Ananda; Dinarti, Riska Putri; Rokmah, Dhaful Oktaviatul; Freitas Marcal, Ivonia Auxiliadora (Jurnal Bina Bangsa Ekonomika, 2025)
International trade begins with differences in resources owned by each country, international trade is defined as trade between or across countries, which includes export and import activities. In this international trade is divided into two categories, namely trade in goods (physical) and trade in services. The purpose of this study discusses the advantages and disadvantages of importing foreign goods for the Indonesian economy and understands the role of the government in regulating imports to protect the development of domestic industry. The method used in this study is a qualitative descriptive method, namely a type of research that aims to provide an overview or explanation of the advantages and disadvantages of importing goods for Indonesia and uses data collection in the form of literature studies by analyzing various journal sources, as well as analysis of documents from the Central Bureau of Statistics, with a focus on volume, value, and import trends over time. The advantages of imports include increasing the availability of goods, decreasing prices, increasing product quality, and supporting economic growth. However, on the other hand, imports also bring challenges, such as threats to local industry, dependence on other countries, and the risk of a trade balance deficit. The role of the government in regulating imports is crucial to protect domestic industry through protection policies, quality regulations, and promotion of local products.